Perilaku Komunitas Begal Remaja (Studi Faktor dan Upaya Penangulangan Pemerintah di Kota Makassar) - Nursalam Nursalam (JED (Jurnal Etika Demokrasi), 2018)
The main problem of research is the number of begal still in the category of adolescents in the city of Makassar. This study aims to (1) analyze the factors causing the existence of motor gang crimes (begal) in Makassar City, (2) To know the efforts made by the government of Makassar City in the prevention of motor gangs (begal) in Makassar. The type of this research is descriptive qualitative method, data collection is used by direct observation, interview, documentation from result of photo and archives owned by local government. The results of this study indicate that: (1) The factors causing the crime committed by motorcycle gangs in Makassar City are the existence of young age, labile, searching identity, and trying new things, and the lack of attention from parents, bad environmental factors, taking illegal drugs to drinking. (2) The efforts of the government and the police in tackling crimes committed by motorcycle gangs in Makassar City, including preventive and repressive efforts. In addition, public participation in general and the role of social and educational institutions.Keywords: Effectiveness, Government Regulation, Begal Behavior